The Development of Modelling Technique Guidelines to Improve Career Planning of Vocational School Students in Samatiga and Johan Pahlawan Districts, West Aceh Regency - Hidayati, Zatil; Budi Astuti, Budi Astuti (International journal of multicultural and multireligious understanding, 2025)
Career problems experienced by students when choosing a career require more understanding when making their choices. To minimize these problems, it is necessary to provide career guidance services with optimal technical variations to make it easier for guidance and counseling teachers to provide services in career planning. For this reason, guidelines are needed to overcome career problems to plan the right career.  This research aims to produce modelling technique guidelines that are feasible and effective in improving career planning for vocational School Student. This research was development research proposed by Brog and Gall with seven steps, namely 1) preliminary research and information collection, 2) planning, 3) initial product development, 3) initial field test, 4) revision of initial field test results, 5) main field trial, and 6) revision of main field test results. Data collection used material validation test questionnaires, media validation test questionnaires, guidance and counseling teacher test questionnaires, interviews, documentation, and career planning scales. Material experts, media experts, and guidance and counseling teachers carried out the feasibility test of the guide. The population in this study amounted to 76 students, and the subject of a trial of 10 guidance counseling teachers was used to determine this study's effectiveness level. The data analysis technique used quantitative dataanalysis. The results of this study show that: 1) the guidance of modeling techniques to improve students' career planning based on the results of the assessment of material experts obtained a score of 73 with the feasible category; the results of the assessment of media experts obtained a score of 83 with the feasible category; and all guidance and counseling teacher practitioners give a score with a range of 69 ≤ S ≤ 84 with the very feasible category; 2) the modeling technique guide to improve students' career planning is effective based on the career planning scale. The effectiveness test conducted on 76 students resulted in an average score of 31.26 for the pretest and 41.2 for the posttest, so it can be concluded that the modeling technique guidebook for career planning is declared effective.